2020
DOI: 10.3390/nu12092738
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Evidence: Influence of Nutritional and Nutrigenetic Factors on Immunity in the COVID-19 Pandemic Framework

Abstract: The pandemic caused by the new coronavirus has caused shock waves in many countries, producing a global health crisis worldwide. Lack of knowledge of the biological mechanisms of viruses, plus the absence of effective treatments against the disease (COVID-19) and/or vaccines have pulled factors that can compromise the proper functioning of the immune system to fight against infectious diseases into the spotlight. The optimal status of specific nutrients is considered crucial to keeping immune components within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
174
2
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(195 citation statements)
references
References 168 publications
(218 reference statements)
0
174
2
19
Order By: Relevance
“…A study on Vietnam’s policy response found that their political readiness, timely communication of information, and cooperation between government and citizens led to an effective response [ 33 , 34 ]. Government preventive responses to mitigate unexpected health outcomes from COVID-19 control measures include specific plans to protect vulnerable populations, such as the elderly, who are most likely to suffer from physical and mental health crises and nutritional insufficiencies from institutional care and self-isolation [ 35 , 36 ]. These findings show a mixed result of government improvement, but still show gaps in governmental responses to viral outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…A study on Vietnam’s policy response found that their political readiness, timely communication of information, and cooperation between government and citizens led to an effective response [ 33 , 34 ]. Government preventive responses to mitigate unexpected health outcomes from COVID-19 control measures include specific plans to protect vulnerable populations, such as the elderly, who are most likely to suffer from physical and mental health crises and nutritional insufficiencies from institutional care and self-isolation [ 35 , 36 ]. These findings show a mixed result of government improvement, but still show gaps in governmental responses to viral outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, despite there being no solid evidence of specific nutrients that could benefit the prevention or treatment of COVID-19, nutritional modulation of the immune system could play an important role across lifespan, which is especially relevant in older adults due to the impact of COVID-19 on this age group [ 20 , 21 ]. Omega-3 polyunsaturated fatty acids and probiotics have been related to anti-inflammatory response and increased resistance to upper respiratory infections [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, despite there being no solid evidence of specific nutrients that could benefit the prevention or treatment of COVID-19, nutritional modulation of the immune system could play an important role across lifespan, which is especially relevant in older adults due to the impact of COVID-19 on this age group [ 20 , 21 ]. Omega-3 polyunsaturated fatty acids and probiotics have been related to anti-inflammatory response and increased resistance to upper respiratory infections [ 20 , 22 ]. Some research suggest that dietary supplementation with vitamins A, B, C, and D as well as minerals such as selenium, zinc, and iron, omega-3, and melatonin could play a role as co-adjuvants in the treatment of COVID-19 patients and for the prevention of upper respiratory tract infections, although evidence is limited [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The holistic approach of maintaining an adequate nutritional balance with healthy eating habits and keeping an active lifestyle are likely to reduce the disease burden of the COVID-19 pandemic [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] . Without the mass availability of effective vaccines or specific drugs to treat or control COVID-19 infection, social distancing and home isolation are the most recommended measures employed to minimize the spread of COVID-19-associated infection.…”
Section: Discussionmentioning
confidence: 99%